Mama bear : one black mother's fight for her child's life and her own - Smith, Shirley; Lockhart, Zelda (Harper, an imprint of HarperCollinsPublishers, 2021)
The wife of NBA Champion and All-Star J.R. Smith shares the story of giving birth to one of the youngest premature babies to survive, shining a spotlight on the dangers Black women face during pregnancy and paying tribute to black women's resilience.